Acanthus ebracteatus leaf extract provides neuronal cell protection against oxidative stress injury induced by glutamate - Anchalee Prasansuklab; Tewin Tencomnao (BMC, 2018)
Abstract Background Acanthus ebracteatus (AE), an herb native to Asia, has been recognized in traditional folk medicine not only for its antioxidant properties and various pharmacological activities but also as an ingredient of longevity formulas. However, its anti-neurodegenerative potential is not yet clearly known. This work aimed to evaluate the protective effect of AE leaf extract against glutamate-induced oxidative damage in mouse hippocampal HT22 cells, a neurodegenerative model system due to a reduction in glutathione levels and an increase in reactive oxygen species (ROS). Methods Cell viability, apoptosis, and ROS assays were performed to assess the protective effect of AE leaf extract against glutamate-induced oxidative toxicity in HT22 cells. The antioxidant capacity of AE was evaluated using in vitro radical scavenging assays. The subcellular localization of apoptosis-inducing factor (AIF) and the mRNA and protein levels of genes associated with the nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant system were determined to elucidate the mechanisms underlying the neuroprotective effect of AE leaf extract. Results We demonstrated that AE leaf extract is capable of attenuating the intracellular ROS generation and HT22 cell death induced by glutamate in a concentration-dependent manner. Co-treatment of glutamate with the extract significantly reduced apoptotic cell death via inhibition of AIF nuclear translocation. The increases in Nrf2 levels in the nucleus and gene expression levels of antioxidant-related downstream genes under Nrf2 control were found to be significant in cells treated with the extract. Conclusions The results suggested that AE leaf extract possesses neuroprotective activity against glutamate-induced oxidative injury and may have therapeutic potential for the treatment of neurodegenerative diseases associated with oxidative stress.